Comparative pharmacokinetics study of two different clindamycin capsule formulations: a randomized, two-period, two-sequence, two-way crossover clinical trial in healthy volunteers - Sanki, Utpal Kumar; Mandal, Badal Kumar; Chandrakala, Venkatesh (Arzneimittelforschung, 2011)
The comparative pharmacokinetic (PK) study of two brands of clindamycin hydrochloride (CAS 21462-39-5) was carried out on 32 healthy Indian subjects in an open label randomized, two way crossover, two period, two sequence, two treatment trial with a minimum washout period of 7 days. Plasma samples were collected at 10 min interval for the 1st hour, at 1 h interval for the next 6 h, at 2 h interval for next 12 h and finally at the 24th hour (pre-dose as baseline value) after drug administration. The concentrations of clindamycin in plasma were determined using high performance liquid chromatography (HPLC) technique with UV detector [lower limit of quantitation (LLOQ) 0.05 μg · mL−1). All PK parameters were calculated from data on clindamycin content in plasma using a non-compartmental model. Primary PK parameters were maximum plasma concentration (Cmax), area under the curve from zero to tth hour (AUCT) and area under the curve from zero to infinite (AUCI), whereas secondary PK parameters were elimination half-life (thalt), elimination rate constant (Kel) and time to reach maximum plasma concentration (Tmax). All primary PK parameters (log transformed) were subjected to ANOVA analysis and two one-sided Student’s t-test (TOST) to construct the 90% confidence intervals. The result of ANOVA showed that all primary PK parameters at 90% confident intervals were within the limit of 80–125%. All the values such as 95.7–109.00% for Cmax( 99.5–117% for AUCT and 99.1% to 114% for AUCI showed pharmacokinetic equivalence and indicated that this comparative pharmacokinetic study was well designed to conclude that the test formulation and reference formulation were pharmaco-kinetically equivalent and hence bioequi-valent with respect to rate and extent of absorption.
Keywords: Bioequivalence; Clindamycin; Macrolide antibiotic; Pharmacokinetics